Analysis and Expansion of the Role of the Escherichia coli Protein ProQ - Sheidy, Daniel T.; Zielke, Ryszard A. (PLOS ONE, 2013)
The decrease in proline transport by the proline porter ProP in a ΔproQ strain has been well documented; however, the reason for this phenotype remains undefined. Previous studies have speculated that ProQ facilitates translation of proP mRNA. Here, we demonstrate that ProQ is enriched in the polysome fractions of sucrose gradient separations of E. coli lysates and the 30S fractions of lysates separated under conditions causing ribosomal subunit dissociation. Thus, ProQ is a bona fide ribosome associated protein. Analysis of proQ constructs lacking predicted structural domains implicates the N-terminal domain in ribosome association. Association with the ribosome appears to be mediated by an interaction with the mRNA being translated, as limited treatment of lysates with Micrococcal Nuclease maintains ribosome integrity but disrupts ProQ localization with polysomes. ProQ also fails to robustly bind to mRNA-free 70S ribosomes in vitro. Interestingly, deletion of proP does not disrupt the localization of ProQ with translating ribosomes, and deletion of proP in combination with the proU operon has no effect on ProQ localization. We also demonstrate that ProQ is necessary for robust biofilm formation, and this phenotype is independent of ProP. Binding studies were carried out using tryptophan fluorescence and in vitro transcribed proP mRNAs. proP is transcribed from two differentially regulated promoters, and ProQ interacts with proP mRNA transcribed from both promoters, as well as a control mRNA with similar affinities. In total, these data suggest that ProQ is positioned to function as a novel translational regulator, and its cellular role extends beyond its effects on proline uptake by ProP.